THE PROBLEM WITH COMPUTER ACCOUNTING ONLINE LEARNING FOR STUDENTS OF SMKN 2 KOTA MADIUN - Supri Wahyudi Utomo; Moh. Ubaidillah; Windarti Windarti (Universitas PGRI Madiun, 2022)
ABSTRACT Online learning is distance learning between students and teachers using laptop/computer/mobile devices and internet networks. Distance learning cannot be separated from the problems faced by students starting from learning facilities, motivation, and learning activities. It will have an impact on students' understanding of accounting computer materials. This study aimed to analyze the problem of online learning regarding motivation, activity, and student learning facilities toward understanding computer accounting learning materials. This research method uses ex post facto primary data using questionnaires distributed to vocational students. The data analysis technique uses SEM analysis with the SmartPLS tool. The results of this study indicate that students' motivation, activity, and facilities significantly positively affect their understanding of learning materials during online learning. ABSTRAK Pembelajaran daring merupakan pembelajaran jarak jauh antara siswa dan guru menggunakan peralatan laptop/komputer/handphone dan jaringan internet. Pembelajaran jarak jauh tidak lepas dari permasalahan-permasalahan yang dihadapi oleh siswa mulai fasilitas belajar, motivasi dan keaktifan belajar. Hal ini akan berdampak terhadap pemahaman siswa terhadap materi komputer akuntansi. Tujuan penelitian ini untuk menganalisis problem pembelajaraan daring ditinjau dari motivasi, keaktifan dan fasilitas belajar siswa terhadap pemahaman materi pembelajaran Komputer Akuntansi. Metode penelitian ini menggunakan penelitian ex post facto data primer dengan menggunakan kuesioner yang disebarkan kepada siswa SMK. Teknik analisis data menggunakan analisis SEM dengan alat SmartPLS. Hasil penelitian ini menunjukkan bahwa motivasi, keaktifan dan fasilitas siswa berpengaruh positif signifikan terhadap pemahaman materi pembelajaran selama pembelajaran daring.